How tourism and pastoralism influence population demographic changes in a threatened large mammal species. (18th June 2013) - Ménard, N.; Foulquier, A.; Vallet, D.; Qarro, M.; Le Gouar, P.; Pierre, J.‐S.
Abstract Pastoralism impacts the habitat quality of wild animals, while poaching is a direct threat to populations. The demographic effects of pastoralism are well known, whereas the effects of poaching are difficult to obtain. In addition, little attention has been paid to the role of tourism as a facilitator of poaching, especially when tourists feed animals and thus lower their fear of humans. In this paper, we investigate the demographic effects of pastoralism (a habitat quality indicator) and tourism (a poaching indicator) on wild Barbary macaques (Macaca sylvanus) in Middle Atlas (Morocco). Neither pastoralism nor tourism affected reproduction rates. High tourism pressure was related to a dramatic deficit in immature individuals. In groups near tourist sites, about half of the infants disappeared suggesting a high poaching pressure on these groups; as poachers select infants to sell as pets, infants used to seeing tourists probably constitute easy poaching targets. Group size and age structure were unrelated to the intensity of pastoralism. Groups were then half the size of those in undisturbed forests and in Middle Atlas 30 years ago. The effects of poaching are predicted to cause a severe collapse of the population. Our results demonstrate the need for Moroccan authorities to be aware of the conservation issues of Barbary macaques and to stop tourists feeding them. This research work illustrates that the potential links between tourism and poaching should be taken into account regarding species conservation, even in protected areas.